A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Age and growth of a habitat‐forming deep‐sea coral Solenosmilia variabilis in the New Zealand region: implications for fisheries management - Dianne M. Tracey; Peter Marriott; Nicholas Hitt; Helen Neil; Malcolm R. Clark (New Zealand Journal of Marine and Freshwater Research, 2025)
One of the most widespread and abundant habitat forming deep‐sea corals in the South Pacific region is Solenosmilia variabilis . The age of this species was assessed using radiocarbon content ( 14 C) on long dead, recently dead, and live branch sections of coral reef matrix sampled from the New Zealand region. Conventional 14 C colony ages (yrs BP), for the living, recently dead, and long dead samples, ranged from 803 to 1186 years (Graveyard Knolls, Chatham Rise), and 907 to 11, 694 years (Louisville Seamount Chain east of New Zealand). Overall calendar ages, ranged from 84 to 292 years, and similar linear and step‐wise growth rate data were obtained. Linear growth ranged from 0.2 to 1.3 mm/yr. From a conservative estimate of matrix height of ∼20 cm, it could take hundreds of years (∼150–660) of growth for a colony of S. variabilis to attain this height, and around ∼2000 years to build a colony diameter of 1 metre. Defining the age, growth and recovery timeframes of deep‐sea coral can inform risk assessments of the level of susceptibility to trawling activity and their potential to recover, as well as provide options for the considered management of deep‐sea habitats.

Small molecule therapeutics for neutralising venom toxins – a drug discovery approach - Laura-Oana Albulescu; Adam Westhorpe; Amy Marriott; Rachel H. Clare; Emma Stars; Nada Mosallam; Daniel Chong-Jun-Weng; Ramachandran Gunasekar; Charlotte A. Dawson; Christopher Woodley; Nivya James; Rohit Patel; et al. (Toxicon, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Age validation and growth of bluenose Hyperoglyphe antarctica using the bomb chronometer method of radiocarbon ageing - P. L. Horn; H. L. Neil; L. J. Paul; P. Marriott (Journal of Fish Biology, 2010)
Age validation of bluenose Hyperoglyphe antarctica was sought using the independent bomb chronometer procedure. Radiocarbon ( 14 C) levels were measured in core micro‐samples from 12 otoliths that had been aged using a zone count method. The core 14 C measurement for each fish was compared with the value on a surface water reference curve for the calculated birth year of the fish. There was good agreement, indicating that the line‐count ageing method described here is not substantially biased. A second micro‐sample was also taken near the edge of nine of the otolith cross‐sections to help define a bomb‐carbon curve for waters deeper than 200–300 m. There appears to be a 10 to 15 year lag in the time it takes the 14 C to reach the waters where adult H. antarctica are concentrated. The maximum estimated age of this species was 76 years, and females grow significantly larger than males. Von Bertalanffy growth curves were estimated, and although they fit the available data reasonably well, the lack of aged juvenile fish results in the K and t 0 parameters being biologically meaningless. Consequently, curves that are likely to better represent population growth were estimated by forcing t 0 to be −0·5.